(untitled) (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2026)
Indonesia requires independent underwater-technology capabilities to support hydrographic survey, subsea infrastructure inspection, oceanographic research, environmental monitoring, search and rescue, and maritime defence. The initial manuscript identified technological gaps, limited laboratories, weak certification arrangements, human-resource constraints, and fragmented stakeholder collaboration. This revised study extends the analysis through a structured narrative review and policy analysis of national planning documents, international standards, and scientific literature on remotely operated vehicles (ROVs), autonomous underwater vehicles (AUVs), navigation, communication, safety, and technology commercialisation. The assessment is organised into six capability dimensions: mission demand, critical technologies, testing facilities, standardisation and assurance, human competencies, and industrial-governance ecosystems. The results indicate that the principal constraint is not merely the ability to build prototypes, but the absence of an end-to-end evidence chain linking user requirements, design, relevant-environment testing, qualification, certification, procurement, and life-cycle support. A national strategy should therefore shift from fragmented prototype projects towards mission-driven programmes supported by open-system architectures, a national network of test facilities, early off-takers, and a Triple Helix governance structure with clear programme ownership. A four-phase roadmap for 2026–2045 is proposed: foundation, integration, industrial scaling, and technology leadership. Each phase is controlled through decision gates and measurable indicators, including technology readiness, domestic content, failure-free operating hours, certified products, qualified personnel, and industrial contracts. The framework provides a basis for research programming, facility investment, procurement reform, and national underwater-technology industrial development.